MicroRNAs in Woody Plants - Fang, Lisha; Wang, Yanmei (Frontiers in Plant Science, 2021)
Abstract: MicroRNAs (miRNAs) are small (~21-nucleotides) non-coding RNAs found in plant and animals. MiRNAs function as critical post-transcriptional regulators of gene expression by binding to complementary sequences in their target mRNAs, leading to mRNA destabilization and translational inhibition. Plant miRNAs have some distinct characteristics compared to their animal counterparts, including greater evolutionary conservation and unique miRNA processing methods. The lifecycle of a plant begins with embryogenesis and progresses through seed germination, vegetative growth, reproductive growth, flowering and fruiting, and finally senescence and death. MiRNAs participate in the transformation of plant growth and development and directly monitor progression of these processes and the expression of certain morphological characteristics by regulating transcription factor genes involved in cell growth and differentiation. In woody plants, a large and rapidly increasing number of miRNAs have been identified, but their biological functions are largely unknown. In this review, we summarize the progress of miRNA research in woody plants to date. In particular, we discuss the potential roles of these miRNAs in growth, development, and biotic and abiotic stresses responses in woody plants.